Brucella Seroprevalence and Associated Risk Factors in Occupationally Exposed Humans in Selected Districts of Southern Province, Zambia - Melai Mubanga (Frontiers Media S.A., 2021)
Background: Brucellosis is a neglected debilitating zoonosis widely recognized as an occupational health hazard. The seroprevalence of human anti-Brucella antibodies in high-risk populations, as well as their risk factors, have not been well-documented in Zambia. This study aimed at estimating the Brucella seroprevalence in herdsmen and abattoir workers and assess the associated risk factors.Methods: A cross-sectional seroepidemiological study was carried out between May and December 2020 among abattoir workers and herdsmen in Namwala, Monze and Choma districts of Southern Province in Zambia. Seroprevalence was assessed by indirect enzyme-linked immunosorbent assay (i-ELISA) or competitive enzyme-linked immunosorbent assay (c-ELISA) while a questionnaire was administered to obtain epidemiological data.Results: A total of 153 individuals were recruited in the study. The overall Brucella seroprevalence was 20.3% (95% CI: 14.6–27.5). Seropositivity among herdsmen and abattoir workers was 14.4% (95% CI: 9.2–21.8) and 46.4%, (95% CI: 28.8–65.0), respectively. Comparable seropositive results among districts showed Namwala with 26.9%, which was the highest, seconded by Monze 19.0%, and the least was Choma with 11.36%, seropositivity. The multivariate logistic regression model showed that occupation, age category, and district of residence were predictors of being seropositive to Brucella spp. antibodies. The odds of abattoir workers being seropositive to Brucella antibodies were 8.6 (95% CI: 2.6–28.2) higher than that of herdsmen being the reference group. The odds of age category 17–50 years being seropositive to Brucella antibodies were 7.0 (95% CI: 0.7–72.2) higher than being <16 years as the reference group. The odds of one having attained primary level of education being seropositive to Brucella were 1.3 (95% CI: 0.1–14.7) or secondary level of education were 6.2 (95% CI: 0.5–72.6) or tertiary level of education were 5.1 (95% CI: 0.2, 113.3) higher than that of no level of education as the reference group. Furthermore, the odds of a respondent being seropositive to Brucella antibodies were 4.5 (95% CI: 1.3–15.7) for Namwala and 4.9 (95% CI: 1.1–21.7) for Monze higher than that of Choma as the reference group.Conclusion: Anti-Brucella antibodies are prevalent among herdsmen and abattoir workers in the study areas of Zambia (20.26%), a sign of exposure to Brucella pathogens. Type of profession, age and level of education seem to influence the exposure to Brucella pathogens. This zoonosis should be considered as one of the differential diagnosis in humans presenting intermittent fever, malaria-like signs and general pain in humans.